Molecular and Multimodal Retinal Imaging Findings in a Multicentric Portuguese Cohort of Stargardt Disease - Geada, Sara (2022)
Introduction Our purpose was to describe the molecular and multimodal retinal imaging findings in a cohort of Portuguese patients with a clinical diagnosis of Stargardt Disease (STGD1).   Methods Multicenter, cross sectional cohort study of consecutive patients with a clinical diagnosis of STGD1, referred from six Portuguese centers. All patients underwent a complete ophthalmological examination complemented by color fundus photography (CFP), fundus autofluorescence (FAF), optical coherence tomography (SD-OCT) and, when available, OCT-angiography (OCTA). Probands with confirmed molecular diagnosis, defined as presenting biallelic mutations classified as pathogenic or likely pathogenic in accordance with the guidelines of the American College of Medical Genetics and Genomics, were divided into three groups according their genotype’s severity.    Results The study included 122 eyes from 61 patients, 54 of which unrelated. Mean age of onset (AO) and mean disease duration were 16.64±12.87 and 20.04±15.21 years, respectively. Confirmed molecular diagnosis was obtained for 26/38 families with available genetic results (diagnostic yield of 68.42%), with the c.1804C>T (p.Arg602Trp) missense variant being the most prevalent (8/26). The less severe genotype group (Group C) was the most frequent (14/26), with a mean AO slightly superior, not statistically significant, to the other groups (B and A). The most frequent CFP pattern was central atrophy with macular and/or peripheral flecks (56 eyes), followed by multiple extensive atrophic changes (n=40). On FAF, 21.05% of the eyes showed a homogeneous background with localized central hypoAF (pattern 1), with the remaining distributing equally through patterns 2 (heterogeneous background of hypo/hyperAF foci and localized central hypoAF) and 3 (multiple areas of hypoAF in a heterogeneous background). Worse visual acuity significantly correlated with advanced CFP and FAF patterns (both p<0.001), reduced central macular thickness (p=0.017), larger foveal avascular zone (p<0.001), reduced density of the superficial (p<0.001) and deep capillary plexuses (p=0.017), and increased area of choriocapillaris atrophy (p=0.007).   Conclusion This study describes the phenotypic and genotypic spectrum of STGD1 in a multicenter Portuguese cohort, revealing a satisfactory detection rate of disease-causing genotypes. The qualitative and quantitative imaging features presented a strong correlation with visual acuity and disease progression and may represent important outcome measures in the evaluation of new therapeutic targets.